2009
DOI: 10.1103/physrevb.80.195314
|View full text |Cite
|
Sign up to set email alerts
|

Defect-induced optical absorption in the visible range in ZnO nanowires

Abstract: The optical properties of ZnO nanowires containing defects are investigated using first-principles densityfunctional theory incorporating the LDA+ U formalism. Calculations include defects in the form of substitutional N, Zn, and O vacancies as well as +1 charged O vacancy. Our calculations reveal that the presence of vacancies contribute strongly to optical absorption in the visible. Furthermore, the presence of +1 charged O vacancy is found to result in a blueshift of the absorption peaks, reducing the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
106
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(116 citation statements)
references
References 18 publications
9
106
0
1
Order By: Relevance
“…18 In addition, DFT studies on nanowires of diameter less than 1 nm assist in understanding the optical properties due to the presence of quantum size effects that generally result in substantial density of states (DOSs) at the band edge. 17 The diameter of the wurtzite ZnO nanowire in the present study is about 1 nm, which is sufficient for examining the relative stability and segregation of Gd, in the V C 2014 AIP Publishing LLC 116, 233906-1 dilute limit. In order to advance the understanding of the magnetic mechanism, we also investigate the electronic structure of these nanowires.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…18 In addition, DFT studies on nanowires of diameter less than 1 nm assist in understanding the optical properties due to the presence of quantum size effects that generally result in substantial density of states (DOSs) at the band edge. 17 The diameter of the wurtzite ZnO nanowire in the present study is about 1 nm, which is sufficient for examining the relative stability and segregation of Gd, in the V C 2014 AIP Publishing LLC 116, 233906-1 dilute limit. In order to advance the understanding of the magnetic mechanism, we also investigate the electronic structure of these nanowires.…”
mentioning
confidence: 80%
“…As it is not computationally feasible to model nanostructures beyond a few nanometers, density functional theory (DFT) studies are often conducted on nanowires of diameters ranging from sub-nanometer to 3 nm in order to study the properties of nanowires and allow comparisons with experimental findings. 16,17 In particular, nanowires of diameter ranging from 1.6 to 5 nm can now be fabricated by experimental techniques. 18 In addition, DFT studies on nanowires of diameter less than 1 nm assist in understanding the optical properties due to the presence of quantum size effects that generally result in substantial density of states (DOSs) at the band edge.…”
mentioning
confidence: 99%
“…It has been shown that oxygen vacancies contribute strongly to optical absorption in the visible spectral and are the origin of the red-shi in the PL emission. [51][52][53][54][55] In these previous studies, it has been discussed that the formation energies of intrinsic defects in ZnO, in particular, oxygen vacancies significantly vary, on the other hand, V which is paramagnetic. The line width changes from 3.0 G in the dark to 1.8 G under UV-LED conditions.…”
Section: -50mentioning
confidence: 99%
“…Considerable efforts have been made to understand native defects in ZnO by theoretical calculations and experiments, since electronic properties are strongly coupled with the local structure and disorder in crystalline materials. [51][52][53][54][55] However, our focus in this study will be on understanding the charge state of the oxygen vacancy. It has been shown that oxygen vacancies contribute strongly to optical absorption in the visible spectral and are the origin of the red-shi in the PL emission.…”
Section: -50mentioning
confidence: 99%
See 1 more Smart Citation